EPISTEMOLOGI PENEMUAN HUKUM NAHDLATUL ‘ULAMA (NU) - Ibnu Elmi A.S Pelu (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2016)
The dynamics of the spirit of ijtihad religious organizations in Indonesia continues to run. Nahdlat al-’’Ulama or NU as a religious organization initiated by KH. Hashim Ash’ari, KH. Hasbullah and KH Wahab. Bisri Samsuri on January 31, 1926 in East Java also has a style and epistemology ijtihad unique to observeThis paper reveals the epistemological model of ijtihad or istinbat al-Ahkam NU. epistemology istinbat al-Ahkam NU using methods ilhaq al-masa’il bi nazairiha. Ilhaq al-masa’il bi nazairiha is to equate the law of a case that does not exist, the books of fiqh as a reference, by the law of a similar issue that has been answered by the text in these books to be based on the elements/pillars ilhaq inside it. Ilhaq epistemology is a modification of the theory of qiyas and pillars inside. Only difference, ilhaq has elements/pillars, namely mulhiq, mulhaq ‘alaih, mulhiq law and’ illat al-hukm. If qiyas was based on the Qur’an and Sunnah, while ilhaq resting on the books of fiqh existing mains.